Analisis Faktor-Faktor yang Mendorong Kepatuhan Wajib Pajak di Kalangan Mahasiswa: Studi Kasus Universitas Pamulang - Astuti, Reni; Muliyani, Muliyani (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to analyze the influence of tax knowledge, tax awareness and the implementation of the e-filling system on taxpayer compliance for the 2024 period, especially for Pamulang University undergraduate Accounting study program students who have studied taxation. The total population with a sample of 214 respondents was followed by students in semesters 2 (two) and 6 (six). This research data was analyzed using multiple linear regression analysis. The data was processed using SPSS 22 which showed the results that the variables of tax knowledge, tax awareness and implementation of the e-filling system simultaneously had a significant effect on taxpayer compliance. Meanwhile the research results of the tax knowledge variable and the implementation of the e-filling system do not have a partially significant effect on taxpayer compliance, and the tax awareness variable has a partially significant effect on taxpayer compliance.